1957
DOI: 10.1111/j.1744-7348.1957.tb00414.x
|View full text |Cite
|
Sign up to set email alerts
|

MOULTING RHYTHM IN THE ALIENICOLAE OF APHIS FABAE SCOP. (HEMIPTERA: APHIDIDAE) IN THE FIELD

Abstract: In a natural population of alienicolae of Aphis fabae Scop. on field beans in July 1952, the frequency of moulting of the last larval instar into the alate form was usually relatively high between about 04.00 and 08.00 hr. G.M.T. This high rate was followed by a decline to a lower fluctuating rate for the rest of the day. T h e moulting rate at night was usually very low.The high rate of moulting in the morning, just as the temperature is rising, may be due to acceleration of nymphal development which leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1957
1957
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Johnson et al [26] reported synchronized molting in aphids, and interpreted this to be caused by the circadian rhythm. Circadian rhythms have also been suggested to be important for synchronizing molt timing in aquatic organisms, for instance, for larval molts in lobsters [27].…”
Section: Discussionmentioning
confidence: 99%
“…Johnson et al [26] reported synchronized molting in aphids, and interpreted this to be caused by the circadian rhythm. Circadian rhythms have also been suggested to be important for synchronizing molt timing in aquatic organisms, for instance, for larval molts in lobsters [27].…”
Section: Discussionmentioning
confidence: 99%
“…These are variously triggered abiotically (for example circadian rhythms in aphids; Johnson et al, 1957) or through active communication (pheromones) (Haug et al, 2013). These mass moultings were succinctly reviewed in Haug et al (2013) for extinct arthropod groups.…”
Section: Mass Moulting Behaviourmentioning
confidence: 99%
“…The experiment on moulting rate The rate of moulting from the last instar nymphs to the adult, on forty-eight leaves along the south and west sides of the crop, was measured at short intervals; the experimental details are given in C. G. Johnson, Haine, Cockbain & Taylor (1957) together with tables of results.…”
Section: The Field Experimentsmentioning
confidence: 99%